Mosaic tapestries : influence of folklores and cultural mores on career choices of refugee populations - a secondary analysis : a thesis presented in fulfilment of the requirement for the degree of Master of Education without specialisation, Massey University, Institute of Education - Nucci, Antonio P. (Massey University, 2020)
The number of refugees is rising dramatically around the globe. Among the key determinants of displacement, refugees are displaced due to violence, brutality, persecution, torture among other crises such as extreme poverty and climate change. Refugees forced to flee their homelands experience numerous challenges when resettling in their host countries. Cultural stories are powerful transmitters of tradition and heritage, they function as a solid knowledge base and motivators for future generations. For displaced communities, cultural stories create a bond through shared stories that serves to enhance their resilience and motivation. Stories are an effective means of reclaiming the past and organising one's future. Subsequently, shaping identity and impacting decision making related to selecting a career path. This study is focused on exploring the influence of folklores and cultural mores on career choices in refugee populations. The initial methodology of interviewing refugees in tertiary studies was modified into a secondary analysis of existing literature due to lack of gaining participants despite contacting tertiary providers nation-wide. The secondary analysis from a very sparse field of literature identified three global themes that were most influential in the career choices of refugees: 1) Familial traditions and cultural heritage both shape identity and are shaped by identity; 2) Agency is acquired through education; and 3) Adversity is relational and transformative. Implications from the study are discussed. The lack of New Zealand based study on refugee population is highlighted along with an overall dearth in literature internationally on the topic.
Keywords: 441013 Sociology of migration, ethnicity and multiculturalism